A design procedure to size thermodynamically-balanced humidification-dehumidification desalination systems. (15th November 2020) - Elzayed, Mohamed S.; Ahmed, M.A.M.; Qasem, Naef A.A.; Antar, Mohamed A.; Zubair, Syed M.
Highlights: A novel thermodynamic balancing technique is used to study the thermal performance. The design of a balanced desalination system with and without extractions is examined. Design calculations of zero-, single-, and double-extraction systems are explained. Heat and mass transfer areas with extraction are higher than the base system. Design procedure can be used for sizing the balanced desalination system. Abstract: Humidification-dehumidification desalination systems are best suited for small-scale and off-grid applications. The primary drawback of humidification-dehumidification systems is their low thermal performance. Thermodynamic balancing of the heat and mass exchange processes between the humidifier and dehumidifier can substantially improve their performance. The optimal thermal design is still needed; thus, the present study mostly focuses on the design of a thermodynamically-balanced system both with and without extractions. This study starts with the implementation of the temperature-enthalpy diagram model to investigate the effect of system enthalpy pinch and minimum and maximum saltwater temperatures on the performance of zero-, single-, and double-extraction systems. After that, design details are investigated to determine the size of the humidifier and dehumidifier under various conditions and power requirements. It is found that the system performance increases as a function of the heat and mass transfer areas (energy effectiveness) of the humidifier and dehumidifier. The systems' performance is represented by the gained output ratio, recovery ratio, energy effectiveness, and enthalpy pinch. The gained output ratio of the single- and double-extraction systems is better than that of the zero-extraction system by a factor of 91% and 112%, respectively. The areas of the single- and double-extraction systems are larger than that of the zero extraction system by a factor of about 51% and 80%, respectively.